Effect Of Empty Fruit Bunches (EFB) Based Lignin On The Properties Of Epoxy EFB Fiber Composite - Mahadar, Marliana Mohd (2011)

(untitled)
Epoxy resin is an important matrix resins for thermosetting polymer composites. The objectives of this study were to extracts and characterize lignin from black liquor to be used as curing agent in epoxy resin application. Lignin obtained from pulping of oil palm biomass empty fruit bunches (EFB) fibers, were used as curing agent in green epoxy composites. The chemical structures and properties of lignin were confirmed by CHN analyses, FTIR, GPC and thermal analysis. Epoxy-lignin composites, with varying lignin content (15%, 20%, 25% and 30%), reinforced with EFB fiber were prepared.